2010
DOI: 10.1038/hdy.2010.58
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA variation in the malaria vector Anopheles minimus across China, Thailand and Vietnam: evolutionary hypothesis, population structure and population history

Abstract: The effects of Pleistocene environmental fluctuations on the distribution and diversity of organisms in Southeast Asia are much less well known than in Europe and North America. In these regions, the combination of palaeoenvironmental reconstruction and inferences about population history from genetic data has been very powerful. In Southeast Asia, mosquitoes are good candidates for the genetic approach, with the added benefit that understanding the relative contributions of historical and current processes to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
54
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 51 publications
5
54
0
Order By: Relevance
“…albopictus populations [74]. We found not only a non-negligible genetic diversity–within the range of that observed in other mosquito species uninfected by Wolbachia [26], [48], [81]–but also an overall concordance between the genetic patterns observed at nuclear and mitochondrial markers; this would not be expected if mtDNA selective sweep had occurred [82]. Previous population genetics studies conducted using allozymes showed significant genetic differentiation between populations at a regional level, but a lack of discontinuity in the geographic distribution of genetic diversity at the level of mainland Asia as a whole [41], [42], [83].…”
Section: Discussionsupporting
confidence: 77%
“…albopictus populations [74]. We found not only a non-negligible genetic diversity–within the range of that observed in other mosquito species uninfected by Wolbachia [26], [48], [81]–but also an overall concordance between the genetic patterns observed at nuclear and mitochondrial markers; this would not be expected if mtDNA selective sweep had occurred [82]. Previous population genetics studies conducted using allozymes showed significant genetic differentiation between populations at a regional level, but a lack of discontinuity in the geographic distribution of genetic diversity at the level of mainland Asia as a whole [41], [42], [83].…”
Section: Discussionsupporting
confidence: 77%
“…One particularly notable result is that selectiondriven phylogeographic structure tends to increase with increasing population size. Many studies have discounted the possibility that phylogeographic breaks arise without geographic barriers because the species under study have large populations (e.g., Chen et al 2011), but the results here show that species with large populations may be particularly likely to show phylogeographic structure when it is driven in part by selection.…”
Section: Discussionmentioning
confidence: 62%
“…In particular, the mitochondrial cytochrome oxidase II gene ( COII ) has been successfully used to study population genetic structure and population history for a wide range of insect species (Krafsur et al, 1999; Sperling et al, 1999; Clements et al, 2000; Franck et al, 2001; Rua et al, 2001; Chen et al, 2004; Chen et al, 2011). In the present study, we sampled populations of An.…”
Section: Introductionmentioning
confidence: 99%